The Study Of Success Factors Of Telekom Malaysia - Abdullah, Baharuddin (2000)
The aim study is to identify factors contributing to the performance of T.M contractors. The focus of the study is on the T.M contractors inthe Northen Region. At the present moment some of the contractors are not performing up to the expectations.